Rumah Kost Di Semarang Dalam Kajian Ekonomi - (Jurusan Teknik Sipil Politeknik Negeri Semarang), Isnadi (Teknis, 2015)
Boarding house in urban development, especially adjacent to the campus is the potential, proven over the years similar businesses increasingly widespread, in the management of a persons generally done as a byproduct of domestic life that at first only as a sideline activity or as a social activity, but as with the progress of time and economic demands, then the business has become a boarding house and a promising business venture, in which the manager has dared to invest, to build him a place which is used as a boarding house business, and by taking a business loan in the bank as additional capital, because in fact the reality is a business that has long-term viability, the results of the economic analysis with the assumption of 20 years is a decent effort and has resulted in the value of profit with (NPV) = Rp.25.109.271, with a value of (BCR) = 1.05 with (IRR) = 15.822 %, payback (break even point) is reached at the age of 15.121 years running businesses. With 16 years already achieved payback, based on the assumption that the land is already available, while building and operating costs obtained with a bank loan. with the results of the economic analysis of the above-mentioned operations perspective boarding house enough to use as a sideline in which management is simple and easy.Keywords: Boarding House, investments, sideline, campus.